Growth with unused capacity and endogenous depreciation - Fabrizio Patriarca; Claudio Sardoni (Levy Economics Institute of Bard College, 2014)
This paper contributes to the debate on income growth and distribution from a nonmainstream perspective. It looks, in particular, at the role that the degree of capacity utilization plays in the process of growth of an economy that is not perfectly competitive. The distinctive feature of the model presented in the paper is the hypothesis that the rate of capital depreciation is an increasing function of the degree of capacity utilization. This hypothesis implies analytical results that differ somewhat from those yielded by other Kaleckian models. Our model shows that, in a number of cases, the process of growth can be profit-led rather than wage-led. The model also determines the value to which the degree of capacity utilization converges in the long run.
Keywords: E12; E25; O40; 330; Kaleckian Models of Growth; Capital Accumulation; Capital Depreciation; Income Distribution and Growth